An evaluation of the policy on incentives: to what extent do incentives enhance the policy objectives of South Africa? - Batwa, Lindile Matthews (Department of Finance and Tax, 2025)
The global trends show that developing countries and economies in transition such as South Africa are now primary foreign direct investment (FDI) destinations, and their importance as FDI recipients continues to increase. This research paper evaluates the usefulness of incentives in driving the investment policy direction of South Africa, the role of stakeholders involved in incentive schemes, and the impact on the tax base. It contributes to the assessment of the usefulness of incentives in enabling the government to achieve its policy objectives. This research commends the government's approach to drafting its policy objectives in line with National Development Plan 2030. It is a plan that has consideration of global trends, and it is an appropriate panacea for the domestic policy framework that brings about foreign direct investment through initiatives such as incentives. Tax incentives are not the primary determinant of the decision to invest. Most investors base their investment decisions not only on economic and commercial factors. Incentives function as a reward to investors who would invest without incentives rather than encouraging investors who would otherwise not invest or go elsewhere. It is clear that non-tax incentive considerations outweigh tax incentive considerations, but it is also argued that tax incentives could effectively address environmental challenges and change consumer behaviour. However, these incentives are generally more effective in combination with other policy instruments. Furthermore, this research finds that — because of the corruption or perception thereof — the deteriorating economic environment has exerted huge pressure on South Africa's public debt, due to the pressure placed on the government to finance its budget. The fiscal challenges that South Africa faces cannot be solved with ‘more' incentives but rather a strategic balance with other measures. The scale and variety of South Africa's investment incentives will continue to be a contested debate. However, while it is also clear that the revenue base is shrinking, it is difficult to envisage an investment policy strategy without incentive schemes. Incentives should be seen not as a problem and a drain on the fiscus but as an integral part of the solution.